Mobile personal health care system - Tang, Szu Lip (2022)

(untitled)
This project is a personal health care system for the mobile platform that aims to helps people to maintain a healthy lifestyle and is also convenient for users to purchase health-related products online. It will provide users with the methodology, concept, and process to keep fit. Since health guidance and workouts are well suited for everyone, it is therefore included in this project. From the design point of view, the focus is on a complete guidance process for users to maintain a healthy lifestyle. It involves four primary categories, namely trackers, health tips, workouts, and online store. The tools used in this project are Android Studio and Firebase. The system is implemented to enhance the information credibility, reduce the waste of physical shopping, and improve health management. This system provides a platform for the users to access all the functions and features for free.